Location, number and factors associated with cerebral microbleeds in an Italian-British cohort of CADASIL patients. - Serena Nannucci; Valentina Rinnoci; Giovanni Pracucci; Andrew D MacKinnon; Francesca Pescini; Poneh Adib-Samii; Silvia Bianchi; Maria Teresa Dotti; Antonio Federico; Domenico Inzitari; Hugh S Markus; Leonardo Pantoni (PLoS ONE, 2018)
The frequency, clinical correlates, and risk factors of cerebral microbleeds (CMB) in Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) are still poorly known. We aimed at determining the location and number of CMB and their relationship with clinical manifestations, vascular risk factors, drugs, and other neuroimaging features in CADASIL patients.We collected clinical data by means of a structured proforma and centrally evaluated CMB on magnetic resonance gradient echo sequences applying the Microbleed Anatomical Rating Scale in CADASIL patients seen in 2 referral centers in Italy and United Kingdom.We evaluated 125 patients. CMB were present in 34% of patients and their presence was strongly influenced by the age. Twenty-nine percent of the patients had CMB in deep subcortical location, 22% in a lobar location, and 18% in infratentorial regions. After adjustment for age, factors significantly associated with a higher total number of CMB were hemorrhagic stroke, dementia, urge incontinence, and statins use (this latter not confirmed by multivariate analysis). Infratentorial and deep CMB were associated with dementia and urge incontinence, lobar CMB with hemorrhagic stroke, dementia, and statins use. Unexpectedly, patients with migraine, with or without aura, had a lower total, deep, and lobar number of CMB than patients without migraine.CMB formation in CADASIL seems to increase with age. History of hemorrhagic stroke, dementia, urge incontinence, and statins use are associated with a higher number of CMB. However, these findings need to be confirmed by longitudinal studies.